The effectiveness of participatory training on reduction of occupational injuries: a randomised controlled trial. (19th October 2011) - Yu, Ignatius; Yu, Wenzhou; Li, Zhimin
Abstract : Objectives: Health and safety training is widely adopted as a means for reducing occupational injuries, but the effectiveness has not been adequately evaluated. Methods: We evaluated the effectiveness of participatory training and didactic training in preventing occupational injuries with a randomised controlled trial among 3479 frontline workers in 60 factories in Shenzhen, China. Work injury data over the preceding 12 months at baseline and 1 year after training were collected and compared, and logistic regression analysis was used to explore the associations between injury and relevant factors. Results: At baseline, the risk of injury increased significantly for workers who worked over 55 h per week (OR=1.57, 95% CI 1.16 to 2.13), with high stress level (OR=3.85, 95% CI 1.87 to 7.92) and a past work injury history (OR=4.28, 95% CI 2.97 to 6.17). The follow-up rate was 60.9% (2120/3479) at 1 year after training. The person-based incidence rate of injury in the intervention group decreased from 89.3 per 1000 workers at baseline to 52.1 per 1000 workers 1 year after training (χ 2 =6.703, p=0.01). The event-based incidence rate of injury in the intervention group also reduced significantly (z=4.543, p<0.01): from 138.3 per 1000 person-years at baseline to 67.0 per 1000 person-years 1 year after training. The injury rates also decreased after 1 year in the control groups, but the decreases were not statistically significant. Conclusions: Long work hours and high stress level could increase the risk of occupational injury. Participatory training was more effective in reducing occupational injuries than didactic training.